PENGARUH PENERAPAN METODE SQ4R (SURVEY, QUESTION, READ, REFLECT, RECITE, REVIEW) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PAI di SMPN 1 IV KOTO AGAM - M. Alexander; Deswalantri; Fajriyani Arsya (CV. ADIBA AISHA AMIRA, 2025)
This research was motivated by PAI subject teachers not optimizing existing training procedures. Not only that, teachers do not have variations in delivering modules to students. Cases of small learning outcomes are very visible when students are asked to repeat the modules they are given. In this observation, students, if many students do not pay attention when the teacher guides, shows the lack of attention and explanation for this PAI training. Students' practice results are below the minimum completeness benchmark. The aim of this research is to find out how much impact the application of the SQ4R procedure has on the learning outcomes of students at SMP N 1 IV Koto. This research is quantitative research using the Quasi Experiment concept. The illustration of this research is 54 students, students VII. 1 27 students (Experimental Category which uses the SQ4R method) and students VII. 2 27 students (Supervision category using conventional procedures). The information analysis method uses a Normality Experiment using the Shapiro Wilk method, and a Homogeneity Experiment using Fisher's Experiment followed by a Hypothesis Experiment with Paired Illustrated T-Test Experiments. The research results prove that based on the results of the information processing it can be concluded that there is an important impact on the application of the SQ4R procedure as well as these results confirm that the research category number Sig. (2-tailed) = 0.00. On the other hand, research alpha = 5% or 0, 05. This means that the Sig number (2-tailed) is smaller than the alpha number (0.00≤ 0.05) so that Ho is rejected and Ha is obtained. This means that there is a consequence of the application of the sq4r procedure on the students' learning results in PAI lessons at SMPN 1 IV Koto category VII.